Kehadiran Dan Kemuliaan Bani Umayyah : Analisis Penanaman Nilai-Nilai Multikultural Dalam Sejarah Peradaban Islam - Renal Sipangidoan Siregar; Sefti Triani; Ririn Rizki Apdasuli; Alimni Alimni (UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to examine the presence and glory of the Umayyad Dynasty: As an effort to instill multicultural values in the history of Islamic civilization. The research method used is a literature study, which involves analysis and synthesis of various sources of literature related to this topic. In this study, an in-depth review of academic literature, books, articles, and relevant official documents related to multicultural values during the Umayyad civilization was conducted. The results of the analysis that the researcher studied show how the role of the Umayyad Dynasty provided multicultural values in its civilization. Based on the search for multicultural values during the Umayyad era, it was found that there were several characteristics of multiculturalism during the Umayyad era such as upholding tolerance and giving rights and obligations to minority religions at that time. Finally, by reflecting on the process and dynamics of the growth and development of multicultural values in the Umayyad dynasty, it is hoped that it can provide benefits and is expected to enlighten the thoughts of readers, especially for theorists and practitioners of Islamic education.